Subclinical Atherosclerosis in Primary Sjögren's Syndrome: Does Inflammation Matter? - Bartoloni, Elena; Alunno, Alessia; Cafaro, Giacomo; Valentini, Valentina; Bistoni, Onelia; Bonifacio, Angelo Francesco; Gerli, Roberto (Frontiers in Immunology, 2019)
Sjögren’s syndrome (SS) is a systemic autoimmune disease mainly characterised by inflammatory involvement of exocrine gland. Atherosclerosis is a complex process leading to plaque formation in arterial wall with subsequent cardiovascular (CV) events. Recently, numerous studies demonstrated that SS patients bear an increased CV risk. Since activation of immune system is a key element in atherosclerosis, it is interesting to analyse whether and how the autoimmune and inflammatory events characterising SS pathogenesis directly or indirectly contribute to atherosclerosis risk in these patients. An increase in circulating endothelial microparticles and integrins, which may be a consequence of endothelial damage and impaired repair mechanisms, has been demonstrated in SS. Increased endothelial expression of adhesion molecules with subsequent infiltration of inflammatory cells into arterial wall is also a critical event in atherosclerosis. The early inflammatory events taking place in the atherosclerotic plaque cause an increase in alarmins, such as S100A8/A9, which seems to be associated with SS disease activity and, in turn, induce up-regulation of interleukin (IL)-1β and other pro-atherogenic cytokines. Interestingly, increased IL-1β levels were also detected in tertiary lymphoid structures developing in vessel adventitia adjacent to the atherosclerotic plaque, suggesting a direct role of IL-1 in this process. Similar to these structures, germinal centre-like structures arising in SS exocrine glands are also tertiary lymphoid systems where T-helper (Th) cell subsets govern the adaptive immune response. Th1 cells are the most prevalent subtype and have been shown to be strongly involved in both SS pathogenesis and atherosclerosis. Th17 cells are attracting great interest and few studies showed its importance in SS development. Albeit in low amounts, a Th17 signature was also detected in atherosclerotic plaques and some animal models demonstrated a significant pro-atherogenic role and positive effects of IL-17A blockade. Despite the fact that T cells have a pivotal role in the inflammatory process that ultimately leads to atherosclerosis, B cells have also been detected in atherosclerotic plaques, although their exact role is still mostly unknown with studies showing contrasting results. In this scenario, the role of inflammation in atherosclerosis pathogenesis in patients with SS needs to be further explored.